2020
DOI: 10.1111/iej.13364
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular diseases and apical periodontitis: an umbrella review

Abstract: Background The existence of an association between cardiovascular diseases (CVDs) and apical periodontitis (AP) remains unclear because results obtained from previous clinical studies and reviews are inconsistent or inconclusive. Objective To conduct an umbrella review to determine whether there is an association between CVDs and the prevalence of AP in adults. Methods The protocol of the review was registered in the PROSPERO database (CRD42020185753). The literature search was conducted using the following el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
(84 reference statements)
2
46
0
2
Order By: Relevance
“…As the highest level of secondary evidence, only two umbrella reviews dealt with the potential bi‐directional association between apical periodontitis and systemic diseases. Nagendrababu et al (2020) revealed that diabetes mellitus is associated with a reduced outcome for root canal treatment, while Jakovljevic et al (2020b) demonstrated the existence of a weak association between apical periodontitis and cardiovascular diseases. The principle problems facing systematic reviews in this field are related to methodological shortcomings of the available primary studies, including inappropriate study designs, unjustified sample sizes, unmatched study groups, inadequate markers and/or surrogate models, unadjusted confounding factors, incomparable results, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the highest level of secondary evidence, only two umbrella reviews dealt with the potential bi‐directional association between apical periodontitis and systemic diseases. Nagendrababu et al (2020) revealed that diabetes mellitus is associated with a reduced outcome for root canal treatment, while Jakovljevic et al (2020b) demonstrated the existence of a weak association between apical periodontitis and cardiovascular diseases. The principle problems facing systematic reviews in this field are related to methodological shortcomings of the available primary studies, including inappropriate study designs, unjustified sample sizes, unmatched study groups, inadequate markers and/or surrogate models, unadjusted confounding factors, incomparable results, among others.…”
Section: Discussionmentioning
confidence: 99%
“…In an umbrella review, Nagendrababu et al (2020) reported that diabetes mellitus was associated with a reduced outcome for root canal treatment and should be considered as a negative preoperative prognostic factor. In a separate umbrella review, Jakovljevic et al (2020b) reported the existence of a weak association between apical periodontitis and cardiovascular diseases, with the weak association probably due to the small number of primary studies and the significant methodological inconsistencies between them.…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic infections were also recorded to be statistically associated with cardiovascular diseases [17]. Therefore, there is a persistent need for resolving this oral health condition since there is an increasing evidence of the association between AP and impaired systemic health [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…CVDs originate from inflammatory endothelial dysfunction (Bergandi et al, 2019) under the significant impact of risk factors such as age, smoking, hypertension, dyslipidaemia, diabetes and sedentary lifestyle (Venturelli et al, 2015). However, in the last decade, studies have analysed the link between CVD and apical periodontitis (AP), and revealed that the quality of the available evidence was limited, and a causal relationship could not be determined (Berlin‐Broner et al, 2017; Jakovljevic et al, 2020a; Jiménez‐Sánchez et al, 2020). AP is a periapical inflammatory process induced by microbial infection of the root canal system (Messing et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In chronic AP, microbiological agents and their products may stimulate local inflammation in arterial walls, activate immunoinflammatory responses and cause cellular alterations leading to the formation of atherosclerotic plaques. Such increased inflammation, in most instances, may cause rupture and thrombus creation leading to ischaemia and infarction of the affected tissues (Jakovljevic et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%